2022
DOI: 10.3390/su14073912
|View full text |Cite
|
Sign up to set email alerts
|

A Life Cycle Assessment of Organic and Chemical Fertilizers for Coffee Production to Evaluate Sustainability toward the Energy–Environment–Economic Nexus in Indonesia

Abstract: Coffee is an important agricultural commodity that is branded according to its environmental criteria in the global market. Therefore, Indonesia’s coffee production system needs to be investigated to meet the demand for eco-labeling, which has become a consumer preference. This study aims to assess the comprehensive sustainability evaluation of coffee production nurtured by an organic fertilizing system (OFS), chemical-organic fertilizing system (COFS), and chemical fertilizing system (CFS) that focuses on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 43 publications
3
5
0
Order By: Relevance
“…This study's outcome also agreed with several other research outputs [ 2 , 4 , 5 , 32 , 34 , [44] , [45] , [46] , [47] , [48] , [49] ] who generally and concisely reported that taller plant heights were observed when grown using organic amendments such as forest soil, decomposed coffee husk, farmyard manure, vermicompost, animal and plant biochar etc. This could be because of a huge amount of organic matter and total nitrogen present [ 15 , 17 , 19 , 50 ] which enhance the capacity to easily uptake nutrients [ 42 , 51 ], maintain soil moisture and enhance soil fertility [ 52 , 53 ] that ultimately improves growth media porosity, aeration and water retention capacity [ 54 ].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…This study's outcome also agreed with several other research outputs [ 2 , 4 , 5 , 32 , 34 , [44] , [45] , [46] , [47] , [48] , [49] ] who generally and concisely reported that taller plant heights were observed when grown using organic amendments such as forest soil, decomposed coffee husk, farmyard manure, vermicompost, animal and plant biochar etc. This could be because of a huge amount of organic matter and total nitrogen present [ 15 , 17 , 19 , 50 ] which enhance the capacity to easily uptake nutrients [ 42 , 51 ], maintain soil moisture and enhance soil fertility [ 52 , 53 ] that ultimately improves growth media porosity, aeration and water retention capacity [ 54 ].…”
Section: Resultssupporting
confidence: 90%
“…The earlier days of 50 % emergence (59.89 ± 20.71) were observed at a depth of 2 cm whereas the delayed seedling emergence (63.65 ± 20.44) was found at 3 cm sowing depth ( Table 3 ). In line with the current study, some authors describe that forest soil and organic fertilizers improve plant emergence velocity and yield enrichment [ [32] , [33] , [34] , [35] , [36] , [37] ]. In addition, seedling emergence in decomposed coffee husk application is more effective compared to using topsoil only [ 5 , 33 , [38] , [39] , [40] , [41] ], probably due to the availability of high organic carbon and the primary macronutrients [ [15] , [16] , [17] , [18] ] and low pH value, bulk and particle density ( Fig.…”
Section: Resultssupporting
confidence: 85%
“…No significant differences are observed for the inclusion of the different cost categories when comparing older studies with studies that have been published more recently. The cost of (some) externalities is only considered in 12 studies (Albizzati et al, 2021;Blanc et al, 2018;Blanc et al, 2019;Canaj et al, 2021a;Canaj et al, 2021b;Dobon et al, 2011;Moosavi-Nezhad et al, 2022;Rahmah et al, 2022;Ribeiro et al, 2018;Ruviaro et al, 2020;Saber et al, 2020;Smith and Lal, 2022) (Fig. 4).…”
Section: Life Cycle Costing Datamentioning
confidence: 99%
“…The increase in FFB will not only boost the export volume that will generate more foreign exchange, but it will also raise farmers' income. In the future, to ensure sustainable agriculture production, it is crucial to take economic sustainability into account [33].…”
Section: Land Swap Optionmentioning
confidence: 99%